2020
DOI: 10.1021/acs.jpcb.0c06747
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Inhibition Mechanism of RNA-Dependent RNA Polymerase (RdRp) of SARS-CoV-2 by Remdesivir and Nucleotide Analogues: A Molecular Dynamics Simulation Study

Abstract: Antiviral drug therapy against SARS-CoV-2 is not yet established and posing a serious global health issue. Remdesivir is the first antiviral compound approved by the US FDA for the SARS-CoV-2 treatment for emergency use, targeting RNA-dependent RNA polymerase (RdRp) enzyme. In this work, we have examined the action of remdesivir and other two ligands screened from the library of nucleotide analogues using docking and molecular dynamics (MD) simulation studies. The MD simulations have been performed for all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Because of the urgency to develop therapeutics, one of the approaches that has been adopted is the drug repurposing of known RNA‐dependent RNA Pol inhibitors such as remdesivir. Several MD studies have already been performed to understand the mechanism of inhibition of remdesivir, which will hopefully aid the discovery of new and more active inhibitors 199–202 …”
Section: Computational Studies Of Polymerase Applicationsmentioning
confidence: 99%
“…Because of the urgency to develop therapeutics, one of the approaches that has been adopted is the drug repurposing of known RNA‐dependent RNA Pol inhibitors such as remdesivir. Several MD studies have already been performed to understand the mechanism of inhibition of remdesivir, which will hopefully aid the discovery of new and more active inhibitors 199–202 …”
Section: Computational Studies Of Polymerase Applicationsmentioning
confidence: 99%
“…In addition to Remdesivir as a therapeutic agent, recently, BioCryst announced a randomized, double-blind, placebo-controlled clinical trial to assess the safety, clinical impact, and antiviral properties of Galidesivir in patients with COVID-19. Computational studies on these inhibitors and their binding with RdRp are also performed to strengthen the COVID19 drug design pipeline (Elfiky, 2020 , 2020 ; Naik et al, 2020 ; Nguyen et al, 2020 ; Wakchaure et al, 2020 ; Wu et al, 2020 ). In view of these developments, this investigation was initiated to determine the atomistic level interaction details of these molecules with RdRp and with the other co-factor proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been reported on the Remdesivir complexed with RNA-polymerase previously and proposed that the protein-inhibitor complex is relatively stable during the simulation, and the equilibration is achieved within 30 ns (Wakchaure et al, 2020 ) . Therefore, to save the computational cost, we extend the simulation for the Remdesivir-bound RdRp to 100 ns.…”
Section: Resultsmentioning
confidence: 99%